Deformable curvature and beam scanning with an elastomeric concave grating actuated by a shape memory alloy - Guerrero, Raphael A (Archīum Ateneo, 2010)
A concave diffraction grating with a tunable radius of curvature R is fabricated by embedding a nitinol wire within an elastomeric grating replica. Curvature of the grating is controlled via the shape memory effect, where strain in the wire is recovered due to martensite–austenite phase transformations induced by resistive heating. The generated force bends the grating into a variable curvature determined by applied current. The radius of curvature for the concave grating is variable from 170 to 44 mm over a current range of 0 to 2.5 A. Actuation of R redirects the grating normal, resulting in a scanning motion of the diffracted beam.